2008
DOI: 10.1007/s11270-008-9726-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Annual Fluxes of Inorganic Constituents in a Small Catchment of a Japanese Cedar Forest near the Sea of Japan

Abstract: Fluxes of major ions in rainfall (RF), throughfall plus stemflow (TF + SF), and stream water (SW) were measured for five water years in a small catchment of a Japanese cedar forest near the Sea of Japan. The fluxes of most ions in RF and in TF + SF, including the non-sea-salt constituents, increased from late autumn to midwinter owing to the seasonal westerly wind. The concentrations of most ions in SW showed no obvious seasonal trend during the study period, whereas NO À 3 concentrations were lowest in summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
35
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 35 publications
11
35
2
1
Order By: Relevance
“…The catchment is characterized by a high loading rate of atmospheric nitrogen, as well as nitrate enrichment of more than 50 µmol L -1 in the stream water eluted from the catchment. Kamisako et al (2008) proposed that atmospheric nitrogen inputs are exceeding the biological demand at this site.…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The catchment is characterized by a high loading rate of atmospheric nitrogen, as well as nitrate enrichment of more than 50 µmol L -1 in the stream water eluted from the catchment. Kamisako et al (2008) proposed that atmospheric nitrogen inputs are exceeding the biological demand at this site.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Details of the Kajikawa experimental forest have been described in past studies (Kamisako et al, 2008;Sase et al, 2012;Sase et al, 2008). Lake Ijira (Fig.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported the impact of land use effect on streams, both in temperate and tropical watersheds (Kamisako et al 2008, Rai et al 2010, Andrade et al 2011. Streams located in undisturbed sites were reported to be more affected by soil characteristics and precipitation, although the streams located in disturbed areas were affected by different sources according to the land use. )…”
Section: Streamwater Chemistrymentioning
confidence: 99%
“…The effects of change in land use on the biogeochemistry have also been described in the literature for both major rivers and streams. It has been shown that these changes affect nitrate, ammonium, calcium, potassium and aluminum concentrations in streams located in temperate (Wang et al 2006, Kamisako et al 2008, Rai et al 2010) and tropical regions (Neill et al 2006, Andrade et al 2011.…”
Section: Introductionmentioning
confidence: 99%